Electro-optic activity of an azopolymer achieved via poling with the aid of silicon nitride insulating layer - Kozanecka-Szmigiel, Anna; Szmigiel, Dariusz; Switkowski, Krzysztof; Schab-Balcerzak, Ewa; Siwy, Mariola (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
Nonlinear optical chromophore was synthesized to form a guest–host system with a PMMA matrix. Thin polymer films were spin-coated onto the substrates containing an additional insulating layer. The layer material was high resistivity and high transmittance silicon nitride obtained by chemical vapour deposition with plasma enhancement at a relatively low temperature of 150 °C. The presence of the nitride layer allowed for performing the polymer poling in the range of high electric field strengths not attained in structures without the insulating layer. Here, for the first time to the best of our knowledge, the silicon nitride interlayer was used in the poling process.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 777-785
Keywords: optyka; azopolymers; polymer poling; electro-optic activity